Adapted physical education and sport - Winnick, Joseph P (Human Kinetics, 2005)
Includes bibliographical references and indexes.; I. Foundational topics in adapted physical education and sport -- II. Individuals with unique needs -- III. Developmental considerations -- IV. Activities for individuals with unique needs.; DVD.; Part I introduces foundational topics in adapted physical education and sport, including program organization and management, adapted sport, individualized programs, and instructional strategies. It helps teachers and leaders to plan, assess, prescribe, teach, and evaluate adapted physical education. Part II explores the unique physical education needs of students with various disabilities. Part III examines developmental considerations, including motor development, perceptual motor development, and considerations for infants and toddlers as well as for early childhood. In part IV the focus is on physical activities and sports for people with disabilities. It includes chapters on rhythmic movement and dance, aquatics, team sports, individual and adventure sports, and enhancing wheelchair sport performance. Each chapter identifies skills, lead-up activities, modifications, and variations to make the experience meaningful, motivating, and fun for the participants. Chapter-opening vignettes and numerous real-life problems that must be solved help readers learn and apply the material.; DVD version of the Brockport Physical Fitness Test video accompanies textbook.